2000
DOI: 10.1108/01443570010304233
|View full text |Cite
|
Sign up to set email alerts
|

Linking operational and environmental improvement through employee involvement

Abstract: This paper uses data from 349 employee involvement (EI) team projects to explore the relationships between process type, operational performance, employee involvement, and environmental performance. We investigate the stated goals and outcomes of EI team projects and relationships among these. For repetitive manufacturing processes in particular, we find strong relationships between the operational goals and outcomes of teams and the positive environmental impact outcome. To the extent that environmental perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(202 citation statements)
references
References 18 publications
(17 reference statements)
4
178
1
9
Order By: Relevance
“…The results also support the contention by Daily, et al (2003Daily, et al ( , 2007 and Daily and Huang (2001) that employees motivated by feelings of empowerment should be expected to be more involved in the improvement of the environment. In particular environmentally conscious organizations should have horizontal organizational structures in place (Daily & Huang, 2001;Govindarajulu & Daily, 2004), be high users of employee involvement practices (Denton, 1999;Fernandez, et al, 2003;Hanna, et al, 2000;Remmen & Lorentzen, 2000) and employ green teams (Beard & Rees 2000;Daily, Bishop & Steiner, 2007;Strachan, 1996). Companies should provide employees continual feedback concerning their impact and effectiveness on environmental improvement efforts (Chinander, 2001;Govindarajulu & Daily, 2004;Ramus 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also support the contention by Daily, et al (2003Daily, et al ( , 2007 and Daily and Huang (2001) that employees motivated by feelings of empowerment should be expected to be more involved in the improvement of the environment. In particular environmentally conscious organizations should have horizontal organizational structures in place (Daily & Huang, 2001;Govindarajulu & Daily, 2004), be high users of employee involvement practices (Denton, 1999;Fernandez, et al, 2003;Hanna, et al, 2000;Remmen & Lorentzen, 2000) and employ green teams (Beard & Rees 2000;Daily, Bishop & Steiner, 2007;Strachan, 1996). Companies should provide employees continual feedback concerning their impact and effectiveness on environmental improvement efforts (Chinander, 2001;Govindarajulu & Daily, 2004;Ramus 2001).…”
Section: Resultsmentioning
confidence: 99%
“…According to May and Flannery (1995) cross-functional teams are crucial for successfully identifying and solving waste problems that exists in different parts of the organization. The responsibility for environmental performance improvement is distributed between operation management, environmental, health and safety (EHS) department, management, R&D, production, purchasing, finance, quality and marketing (Hanna, Newman & Johnson, 2000;Hart, 1995;Zsidisin & Hendrick, 1998). In light of the preceding discussion the following hypothesis is proposed for empirical testing: H2: Employee empowerment will be positively related to perceived environmental performance.…”
Section: Management Commitmentmentioning
confidence: 99%
“…More specifically, several case studies of ISO 14001 certified companies have shown that implementation of the standard has helped reduce environmental impacts, including the volume of waste generated, water and energy consumption, and atmospheric emissions (Chattopadhyay, 2001;Fielding, 1999). Other studies have emphasized the beneficial effects of the standard on technological innovation, improvements in safety procedures and decreases in the risk of environmental mishaps (Hanna et al, 2000;Shin and Chen, 2000), decrease in the use of raw materials, energy, and costs (Chattopadhyay, 2001;Fielding, 1999;González-Benito and González-Benito, 2005;Shin and Chen, 2000), and improvements in the image of organizations, competitive edge, and response to customer expectations (Corbett and Kirsch, 2001;Goh Eng et al, 2006;Melnyk et al, 2003;Potoski and Prakash, 2005;Pun and Hui, 2001). …”
Section: The Instrumental Perspective: a Standard For Improving Envirmentioning
confidence: 99%
“…Employees' environmental initiatives are generally considered to be one of the main success factors in organizational greening (Andersson and Bateman 2000;Hanna et al 2000;Ramus 2001;Ramus and Killmer 2007;Walley and Stubbs 2000;Daily et al 2009). Many studies have demonstrated the close relationship between employee initiatives and the environmental performance of organizations (Boiral 2005).…”
Section: The Contribution Of Employee Initiatives To Corporate Greeningmentioning
confidence: 99%
“…Other studies have shown the importance of employee participation in various green initiatives (pollution prevention, waste management, environmental committees, etc.) for improving environmental performance (Hanna et al 2000;Stone 2000;Boiral 2005Boiral , 2009). The success stories of a number of green organizations (Interface, 3M, Patagonia, etc.)…”
Section: The Contribution Of Employee Initiatives To Corporate Greeningmentioning
confidence: 99%